Hepatic Epithelioid Hemangioendothelioma and Adult Liver Transplantation: Proposal for a Prognostic Score Based on the Analysis of the ELTR-ELITA Registry - Lai, Quirino; Feys, Estelle; Karam, Vincent; Adam, Rene; Klempnauer, Jurgen; Oliverius, Martin; Mazzaferro, Vincenzo; Pascher, Andreas; Remiszewski, Piotr; Isoniemi, Helena; Pirenne, Jacques; Foss, Aksel; et al. (Transplantation, 2017)
BACKGROUND: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare vascular tumor which has an intermediate aggressive behavior. Although the value of liver transplantation (LT) is well established, its place in the management of HEHE is still unclear. The aim of this study is to confirm, based on a very large patient cohort, the value of LT in the management of HEHE and to identify risk factors for post-LT recurrence. METHODS: The outcome of 149 transplant recipients with HEHE recorded in the European Liver Transplant Registry during the period November 1984 to May 2014 was analyzed. Median post-LT follow-up was 7.6 years (interquartile range, 2.8-14.4). RESULTS: Cox regression analysis showed that macrovascular invasion (hazard ratio [HR], 4.8; P < 0.001), pre-LT waiting time of 120 days or less (HR, 2.6; P = 0.01) and hilar lymph node invasion (HR = 2.2; P = 0.03), but not pre-LT extrahepatic disease, were significant risk factors for recurrence. These findings, which were also confirmed in a propensity score analysis, allowed the development of a HEHE-LT score enabling stratification of patients in relation to their risk of tumor recurrence. Patients with a score of 2 or less had a much better 5-year disease-free survival compared to those having a score of 6 or higher (93.9% vs 38.5%; P < 0.001). CONCLUSIONS: The analysis of this (largest in the world) HEHE adult liver recipient cohort clearly confirms the value of LT in the treatment of this rare disorder and also permits identification of patients at risk of posttransplant recurrence. Posttransplant follow-up should take the HEHE-LT score into account. Extrahepatic disease localization is reconfirmed not to be a contraindication for LT.
Keywords: nádory jater; Registries; Hemangioendothelioma, Epithelioid; neoadjuvantní terapie; proporcionální rizikové modely; Humans; Algorithms; lidé středního věku; Proportional Hazards Models; Risk Factors; výběr pacientů; registrace; Multivariate Analysis; Predictive Value of Tests; Patient Selection; Female; rizikové faktory; dospělí; tendenční skóre; přežívání štěpu; Neoplasm Invasiveness; Time Factors; výsledek terapie; lidé; Europe; Liver Neoplasms; seznamy čekatelů; přežití bez známek nemoci; Lymphatic Metastasis; metody pro podporu rozhodování; lymfatické metastázy; časové faktory; epiteloidní hemangioendoteliom; Waiting Lists; Liver Transplantation; transplantace jater; Adult; ženské pohlaví; Kaplanův-Meierův odhad; multivariační analýza; Decision Support Techniques; Male; Middle Aged; prediktivní hodnota testů; Retrospective Studies; Treatment Outcome; algoritmy; Neoadjuvant Therapy; Disease-Free Survival; invazivní růst nádoru; retrospektivní studie; Kaplan-Meier Estimate; lokální recidiva nádoru; Risk Assessment; mužské pohlaví; Graft Survival; Neoplasm Recurrence, Local; hodnocení rizik; Evropa; Propensity Score